2021
DOI: 10.1002/alr.22759
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and cytokine profiles of central‐compartment‐type chronic rhinosinusitis

Abstract: Background The clinical characteristics of central‐compartment‐type chronic rhinosinusitis (CRS) in East Asian individuals are not clear. We sought to investigate the clinical features and the cytokine profiles of central‐compartment‐type CRS in our patient group. Methods Adult patients diagnosed with bilateral CRS were recruited, and patients who had previously undergone sinus surgery and pansinusitis (Lund‐Mackay scores >23) were excluded. Central‐compartment‐type CRS was defined by both endoscopic and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 47 publications
(62 reference statements)
3
39
1
Order By: Relevance
“…In our study, the mean SNOT‐22 score for loss of smell or taste in the CCAD group was higher (2.92 of 5) than that in the LDNP group (1.96 of 5) ( p < 0.01). This result is consistent with a previous study showing that patients with central compartment–type CRS had more hyposmia or anosmia than patients with other types of CRS (37.5% vs 13.7%, p = 0.036) 16 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the mean SNOT‐22 score for loss of smell or taste in the CCAD group was higher (2.92 of 5) than that in the LDNP group (1.96 of 5) ( p < 0.01). This result is consistent with a previous study showing that patients with central compartment–type CRS had more hyposmia or anosmia than patients with other types of CRS (37.5% vs 13.7%, p = 0.036) 16 …”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation is that serum tests for specific allergies have limitations in confirming “local allergic rhinitis.” In other words, some of our patients’ allergic symptoms were limited to the nasal mucosa. A study conducted by Lin et al in Taiwan also showed no significant relationship between allergen sensitization and CCAD 16 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, a study from Taiwan demonstrated that hyposmia or anosmia was the major symptom and more common in the central compartment-type CRS group. 32 The distinct presentations of olfactory dysfunction may attribute to the recruited patients with different stages of CCAD.…”
Section: Discussionmentioning
confidence: 99%
“…A centrally limited sinus inflammation entity on the CT scan has been defined as having normal sinus mucosal or mucosal thickening involving only the floor or medial wall of the ethmoid sinuses ( 25 , 26 ). We previously found that central-compartment-type CRS represented an eosinophilic/type 2 inflammation endotype, with elevated expression of IL-5 and IL-13 in the sinonasal tissues, and patients with this central-compartment subtype of CRS had more smell problems as major symptoms than patients with other CRS subtypes ( 27 ).…”
Section: Olfactory Dysfunction and Chronic Rhinosinusitis Endotypesmentioning
confidence: 99%